Pelatihan Pembuatan Media Pembelajaran Interaktif Berbasis Teknologi untuk meningkatkan Kompetensi Guru - Lisnawita; Lucky Lhaura Van FC; Elvira Asril (JCoos: Journal of Community Outreach in Science & Society, 2026)
Conventional lecture-based still dominates the learning process at one of the vocational high schools (SMK) in Pekanbaru causing students to be less focused and less motivated in participating in teaching and learning activities. This community service program aims to improve teachers’ knowledge and skill in developing interactive learning media using an interactive presentation application. The training was carried out in four stages, namely pre-test, material introduction and explanation, demonstration and practice, and post-test and evaluation. The activity was held at laboratory of the Faculty of Computer Science, Universitas Lancang Kuning, with five teachers as participants. Participants’ level understanding before and after the training was measured using the Guttman Scale. The evaluation result showed an increase in the average level of understanding from 7.50% in the pre-test to 90.50% in the post-test, representing an improvement of 85%. The training proved effective in enhancing teachers’ ability to design interactive learning materials while also fostering their enthusiasm for the use of learning technology